Glabralides A – C, three novel meroterpenoids from Sarcandra glabra. Issue 2 (11th January 2018) - Yang, Wan-qiu; Hai, Ping; Xiao, Han; Gao, Yuan; Tao, Yun-hai; Miao, De-ren; Wang, Fei
Abstract: Glabralides A–C (1–3 ), three novel meroterpenoids including two unprecedented skeletons were isolated from the whole plants of Sarcandra glabr a. Glabralide A (1 ) represented a unique skeleton of the chalcone-coupled monoterpenoid, bearing a bicyclo [2.2.2] octene core unit with five chiral centers. The structures were established by spectroscopic methods, including 2D NMR experiments, and the absolute configurations were determined using circular dichroic (CD) spectra. The plausible biogenetic pathway for1 suggested that α -phellandrene was conjugated with chalcone by Diels-Alder cyclization, and for3 implied that α -phellandrene and o -hydroxy phenylacetate cyclized by an uncommon radical addition and cationic cyclization. Graphical abstract: Highlights: Three novel meroterpenoids were isolated from Sarcandra glabr a. Glabralide A (1 ) and C (3 ) possessed unprecedented skeletons. The absolute configurations were determined by CD spectra. The plausible biogenetic pathways for glabralide A−C were proposed.